Kualitas Pelayanan Publik bagi Masyarakat: Studi Fenomenologi pada Kantor Kecamatan Pati Kabupaten Pati - Rismathul Dinda Aryanti; Aulia Prima Kharismaputra (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
Public service is a key indicator of the quality of government governance. Practices at the subdistrict level still face challenges, such as low responsiveness, unpredictable service times, and unmet community needs. The results of the Community Satisfaction Survey (SKM) indicate high service performance, but do not fully reflect the community’s experience. This study aims to analyze the quality of public services at the Pati Subdistrict Office from the perspective of the community’s experience using a phenomenological approach within the SERVQUAL framework. The study employs qualitative methods, including observation, interviews, and documentation. The results reveal a gap between the theoretical framework of service quality and the reality observed in the field. The SERVQUAL service quality theory identifies responsiveness and reliability as key dimensions; however, in the public’s lived experience, these two are not perceived as dominant. Public satisfaction places greater emphasis on a sense of security (assurance) and staff empathy, while reliability and responsiveness tend to be overlooked. Limitations in facilities and infrastructure (tangibles) result in ineffective service, characterized by the absence of a queueing system and services that are not completed in a single visit. This study indicates that the public’s perception of public service quality prioritizes the final outcome over the service process. Efforts to improve service quality should focus not only on procedural aspects but also on comprehensively addressing the public’s needs and experiences.